Fabrication and Characterization of Polyurethane Foams for Skin Tissue Engineering - Atukeren, Elif Zehra; Tiryaki, Aysegul; Ulag, Songul; Ozturk, Rabia Yilmaz; Cakir, Rabia (WILEY-V C H VERLAG GMBH, 2026)
Skin diseases, such as thermal burns and diabetic leg ulcers, can poredamage the dermal and epidermal layers, depending on injury depth and extent. Infection poses a major risk in these wounds. Wound dressings are essential in treating injured skin, as they shield open wounds from infection-causing external factors and mechanical irritation. In this study, polyurethane (PU) foams were produced via precise casting. Their mechanical, chemical, biological, and morphological properties were characterized, and in vitro biocompatibility tests were conducted with NIH/3T3 cells. The morphological properties of the PU foams were characterized with a scanning electron microscope (SEM). Tensile test proved the mechanical strength of the foams ranging from 1.64 +/- 0.66 MPa to 4.62 +/- 1.22 MPa. Cell culture results detected with the XTT method showed the biocompatibility properties of the foams. XRD analysis demonstrated the amorphous structure of the PU foams. This study is anticipated to lay a foundation for further research on incorporating antibacterial agents, drugs, growth factors, vitamins, peptides, and collagen into polyurethane foam structures.
Keywords: polyurethane foam; skin diseases; therapeutic use; tissue engineering; wound dressing; DRESSING MEMBRANES; IN-VITRO; ANTIBACTERIAL; SCAFFOLDS; GELATIN; SPONGE; MATS; FILM; Chemistry